NATURAL REGENERATION IN MIXED PLANTING FOR ECOLOGICAL RESTORATION IN THE COASTAL PLAIN OF PARANÁ STATE, BRAZIL - Mattar, Eduardo Abilhoa; Nakajima, Nelson Yoshihiro; Ângelo, Alessandro Camargo; Carpanezzi, Antônio Aparecido; Neves, Edinelson Maciel; Britez, Ricardo Miranda (Floresta, 2023)
Pastures occupy approximately 20% of the Brazilian territory and a significant part of these areas are degraded and have legal environmental liabilities. Ecological restoration is necessary to remedy this liability. The objective of the present study was to determine the effectiveness of a forest restoration planting in an area previously used as buffalo pasture, through floristic and phytosociological parameters of natural regeneration. The study area was densely populated by invasive exotic grasses (Urochloa spp.) until 2006, when, after eliminating the grasses, six native tree species were planted at 2.5 × 1.6 m spacing. A total of 73 terrestrial plant species were found, the most important being Alchornea glandulosa Poepp. & Endl. - heliophilous, which showed high abundance in all strata. The restoration methodology employed was effective in triggering natural succession in the study area, resulting, after 12 years, in floristic and structural parameters consistent with the initial stage of development of the alluvial Dense Ombrophylous Forest. It is inferred that the well-preserved landscape in the region has been determinant in providing the propagules and dispersers that made the observed species richness possible, while the planting tends to have contributed with the control of grasses and with the recovery of the forest environment, facilitating the arrival and development of these propagules. Evidence of soil degradation by use as pasture was observed, and in former buffalo bathing areas neither restoration planting nor natural regeneration developed.